FREQUENCY OF PROSTATE CANCER IN PATIENTS UNDERGOING TRANS-URETHRAL RESECTION OF PROSTATE (TURP) FOR CLINICALLY BENIGN SYMPTOMATIC ENLARGED PROSTATE - Anwar, Farid; Mohayuddin, Qazi Nizam; Islam, Muhammad; Aasim, Muhammad; Riaz, Muhammad; Khan, Asad (Journal of Postgraduate Medical Institute, 2012)
Objective: To determine the frequency of carcinoma prostate in patients undergoing trans-urethral resection of prostate (TURP) for clinically benign symptomatic enlarged prostate. Methodology: A descriptive study including all patients who had the clinical symptoms of BPH and operated with TURP in the RMI was designed. The study spanned from June 2009 to June 2010. Patients' data, clinical history, examination and operation notes were saved in a file. All the patients were properly evaluated by the team comprising of the authors pre-operatively. On the basis of these evaluations, a malignancy was not anticipated. All the patients were operated using TURP by the same team under spinal anesthesia. Prostate chippings collected at TURP from each patient were sent as routine, for histopathological evaluation and reporting. Results: Majority of patients (n=44, 66.7%) were older than 60 years. Patients' ages ranged from 48 to 100 years with a mean of 69.5 years. Out of all the patients in this study, 9 patients (13.6%) presented with acute urinary retention and 57 patients (86.4%) presented with Lower Urinary Tract Symptoms (LUTS) and chronic urinary retention. In 9 patients (13.6%) malignancy of the prostate on histopathological examination was confirmed with 8/9 having definitive adeno-carcinoma. Two patients had Gleason score 6/10 and 6 patients had Gleason score 8/10) of the prostate while 1/9 had carcinoma in situ. Out of the 9 patients with malignancy 8 patients (88.9%) were more than 60 years of age while 1 patient (11.11%) was aged 56 years. Conclusion: The substantial proportion of patients with confirmed PCA in patients undergoing TURP for clinically symptomatic benign enlarged prostate emphasizes the need for early diagnosis through histopathological examination.